An Institutional Logics Approach to the Analysis of Social Movement Fields. (March 2015) - Larson, Jeff A.; Lizardo, Omar
How do institutions generate stability within and limited diversity across social movements? To answer this question, we draw on select strands of Institutional Analysis and introduce the concept of institutional movement logics (IMLs), cultural templates made up of combinations of issues, tactics, and targets that provide social movement organizations with a focus of attention, a source of meaning and identity, and a vision of how to "do" contention. Movement organizations can be observed in clusters based on their IMLs that define the dominant set of logics within that field. In this way, IMLs account for patterns of stability and diversity within social movement fields. We provide evidence of the empirical utility of the IML approach with an analysis of Seattle's social movement field between 1999 and 2005. Using scaling methods to elicit clusters of movement organizations by their combinations of issues, tactics, and targets, along with archival and interview data, we find that this field was structured by robust and stable partitions between three distinct IMLs. With this analysis, we advance an institutional logics approach for understanding social movements, showing how Social Movement Theory can concretely benefit from a tighter integration with Institutional Analysis.